Pengaruh Kualitas Pelayanan Dan Harga Terhadap Kepuasan Konsumen Pada Pengguna Gojek Di Kota Solo - Atiska Eka Parya (Institut Teknologi dan Bisnis (ITB) Semarang, 2023)
The purpose of conducting this research is to find out how the influence of service quality and price on consumer satisfaction of Gojek users in Solo City. This research is quantitative using a questionnaire. The sample taking technique in this study used the Leedy formula with a sample size of 100 respondents. The sampling technique used in this research is purposive sampling. The results of this study explain that service quality has a significant effect on consumer satisfaction of Gojek users in Solo City, with a positive regression coefficient meaning that if the quality of service is getting better, then the consumer satisfaction of Gojek users in Solo City has also increased. This study also explains that price has a significant effect on consumer satisfaction of Gojek users in Solo City, with a positive regression coefficient meaning that if prices are cheaper, then Gojek user consumer satisfaction in Solo City has also increased.